Cerebellar and Cerebral Amyloid Visualized by [18F]flutemetamol PET in Long-Term Hereditary V30M (p.V50M) Transthyretin Amyloidosis Survivors - Uneus, Erica Irene; Wilhelmsson, Christer; Bäckström, David; Anan, Intissar; Wixner, Jonas; Pilebro, Björn; Riklund, Katrine; Ögren, Mattias; Ögreen, Margareta; Axelsson, Jan; Suhr, Ole B.; Sundström, Torbjörn (Frontiers in Neurology, 2022)
Introduction Hereditary transthyretin (ATTRv) amyloidosis caused by the V30M (p. V50M) mutation is a fatal, neuropathic systemic amyloidosis. Liver transplantation has prolonged the survival of patients and central nervous system (CNS) complications, attributed to amyloid angiopathy caused by CNS synthesis of variant transthyretin, have emerged. The study aimed to ascertain amyloid deposition within the brain in long-term ATTRv amyloidosis survivors with neurological symptoms from the CNS. Methods A total of 20 patients with ATTR V30M having symptoms from the CNS and a median disease duration of 16 years (8–25 years) were included in this study. The cognitive and peripheral nervous functions were determined for 18 patients cross-sectionally at the time of the investigation. Amyloid brain deposits were examined by [18F]flutemetamol PET/CT. Five patients with Alzheimer's disease (AD) served as positive controls. Result 60% of the patients with ATTRv had a pathological Z-score in the cerebellum, compared to only 20% in the patients with AD. 75% of the patients with transient focal neurological episodes (TFNEs) displayed a pathological uptake only in the cerebellum. Increased cerebellar uptake was related to an early age of onset of the ATTRv disease. 55% of the patients with ATTRv had a pathological Z-score in the global cerebral region compared to 100% of the patients with AD. Conclusion Amyloid deposition within the brain after long-standing ATTRv amyloidosis is common, especially in the cerebellum. A cerebellar amyloid uptake profile seems to be related to TFNE symptoms.